Genetics: A conceptual approach - Pierce, Benjamin A.; Pierce, Benjamin A. (New York, W.H. Freeman, 2017)
With Genetics: A Conceptual Approach, Ben Pierce brings a master teacher$1 (Bs experiences to the introductory genetics textbook, clarifying this complex subject by focusing on the big picture of genetics concepts and how those concepts connect to one another. The new edition continues the Pierce tradition of pedagogical excellence and scientific currency.s
Reference A1-11p.; Glossary C1-C22p.; Index E1-29p.
Keywords: Chromosome variation; Chromosomes and cellular reproduction; Introduction to genetics; Principles of heredity; Zoology